Relationship between parental attachment, social support and life satisfaction among adolescents - Mohamed Pakri, Rini Shafiqa; Ismail, Nellie (Human Resources Management Academic Research Society (HRMARS), 2023)
Both parental attachment and social support are essential factors in the formation of life satisfaction among adolescents. Adolescents with low levels of life satisfaction have been associated with potentially negative consequences, maladaptive behaviours, and school disengagement. Therefore, the objective of this study was to determine the relationship between parental attachment, social support (family and peers), and life satisfaction among adolescents. A total of 440 Form Six students between the ages of 18 and 19 years old were selected from one secondary school in Seremban, Negeri Sembilan by using a multi-stage cluster random sampling technique. Data was collected by using an online questionnaire (Google Form). The Domain of Adolescent Attachment Scale-Malay (DAAS-Malay) was used to measure parental attachment while The Multidimensional Scale of Perceived Social Support (MSPSS) was used to measure social support. Life satisfaction was measured using The Satisfaction with Life Scale (SWLS). The results showed that there were significant positive relationships between maternal attachment, paternal attachment, family support, and peer support with adolescents’ life satisfaction. Meanwhile, multiple regression analysis outcomes indicated that family social support yielded the strongest influence on life satisfaction. In conclusion, parental attachment, family social support, and peer social support are key determinants of adolescents’ life satisfaction.